World Bank Corporate Scorecard, April 2014 - World Bank Group (Washington, DC, 2014)
The World Bank Group Corporate Scorecard is designed to provide a high-level and strategic overview of the World Bank Group s performance toward achieving the two goals. It is the apex from which indicators cascade into the monitoring frameworks of the three World Bank Group institutions. The Scorecard is structured into three tiers. These three tiers are the components of a unified results and performance monitoring framework with indicators grouped along the result chain as follows: the Scorecard monitors, at an aggregate level, how the World Bank Group implements its Strategy and improves its performance (Tier III) in order to support clients in achieving results (Tier II) in the context of global development progress (Tier I).